Industry and occupational employment projections overview and highlights, 2022-32. (Monthly Labor Review, 2023)
The article provides an overview of industry and occupational employment projections and highlights in the U.S. from 2022 to 2023. Data shows projected change in wage, salary employment, employment by occupational group and occupations with the most job growth. It forecasts employment growth in industries including healthcare and social assistance, professional, scientific and technical services, information, transportation and warehousing services, retail trade, fossil fuel and manufacturing.